2020
DOI: 10.1051/e3sconf/202020701021
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and thermodynamic properties of solutions of clary sage (Salvia sclarea L.) essential oil in ethanol-water system

Abstract: Clary sage (Salvia sclarea L.) essential oil-ethanol-water system was investigated. The surface tension, density and refractive index of clary sage essential oil + ethanol (70%, 75%, 80%, 85%, 90%, and 95%) solutions were measured. The chemical composition of solutions (ratio 1:5, 1:6, and 1:7) was determined using GC/MS analysis. According the experimental results ternary phase diagrams were constructed. Comparative revue between experimental and calculated surface tension data was done. After analyses good c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The difference between linalyl acetate and lavender solutions is based on lower values for specific heat capacity, which is probably due to the fact that lavender solutions involve the main components of lavender oil. The obtained results on the coefficient of thermal conductivity and thermal difusivity for solutions of lavender oil-ethanol-water are close to the values for solutions of linalool-ethanol-water presented in [17,22], which is explained by the fact that the components involved in the solutions are oxygen-containing monoterpenes.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The difference between linalyl acetate and lavender solutions is based on lower values for specific heat capacity, which is probably due to the fact that lavender solutions involve the main components of lavender oil. The obtained results on the coefficient of thermal conductivity and thermal difusivity for solutions of lavender oil-ethanol-water are close to the values for solutions of linalool-ethanol-water presented in [17,22], which is explained by the fact that the components involved in the solutions are oxygen-containing monoterpenes.…”
Section: Resultssupporting
confidence: 87%
“…The presented results in Table 2 have shown that all physicochemical dimensions decreased their values when ethanol in solutions increased as quantity. Surface tension and refractive index for pure ethanol are: γ = 22.80 mN.m -1 and ρ = 0.789 kg.m -3 [17]. The values of refractive index presented some small variations in the last solutions prepared with 90% and 95% ethanol.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…2.1.4 Chemical composition of the essential oil. GC analysis was performed using gas chromatograph Agilent 7890A [17] 2.1.5 Thermodynamic and thermal properties of the essential oil and its main compounds. Specific heat capacity is obtained by eq.…”
Section: Methodsmentioning
confidence: 99%